ANALISIS DAMPAK PEMBANGUNAN BENDUNGAN LAUSIMEME PADA KECAMATAN SIBIRU BIRU KABUPATEN DELI SERDANG TERHADAP PRODUKTIVITAS DAERAH IRIGASI - Fahruddin, Muhammad Fiqhri; Franchitika, Rizky; Hutauruk, Denny Meisandy (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2025)
LauSimeme Dam is a multi-purpose dam that functions to prevent flooding in Medan City and its surroundings. The Lau Simeme Dam is located in Kuala Dekah Village, Biru-Biru District, Deli Serdang Regency, North Sumatra. The benefit is that it can meet the raw water needs of Medan City and its surroundings with a supply of 3000 liters per second. The impact of the construction of the LauSimeme dam is a decrease in water quality, obstruction of the flow of nutrients, obstruction of fish migration, and the extinction of local fish species, decreased fertility downstream, loss of agricultural land, breeding of disease seeds, and affecting water temperature. Flooding is a situation where water cannot be accommodated in the drainage channel (riverbed) or the flow of water in the drainage channel is blocked so that it overflows and inundates the surrounding area (floodplain). Rainfall can cause flooding if the rainfall falls with high intensity, for a long duration, and occurs over a wide area. Rainfall data is processed using the Gumbel method, and flood discharge data is processed using the Nakayasu method. Based on rainfall calculations, the distribution used is the Gumbel Distribution with an average value of 134.100 mm. Based on the results of the chi test, all probability distributions tested (Normal, Gumbel, Log Normal, and Log Pearson Type III) have a calculated X2 value smaller than X2cr (5.991). Therefore, all distributions can be